Host-specific microbiome-rumination interactions shape methane-yield phenotypes in dairy cattle - Alejandro Castaneda; Nagaraju Indugu; Kathryn Lenker; Kapil Narayan; Sarah Rassler; Joseph Bender; Linda Baker; Ojas Purandare; David Chai; Xin Zhao; Dipti Pitta (mSphere)
ABSTRACT Enteric methane emissions (EMEs) negatively impact both the environment and livestock efficiency. Given the proposed link between CH4 yield and the rumination time (RT) phenotype, we hypothesize that this connection is mediated by the gut microbiome. This study investigated the RT-microbiome-EME connection using rumination-bolus, fecal, and rumen microbiomes as non-invasive proxies for identifying low-EME cows. High-RT cows ruminated 94 minutes longer per day (20%) and exhibited 26% lower EME than low-RT cows, confirming a strong RT-CH4-yield association. Microbial analysis revealed conserved methanogen diversity across the rumen, bolus, and fecal microbiomes, though functional differences were evident. High-RT cows had a greater abundance of Methanosphaera stadtmanae, suggesting an increased potential for methylotrophic methanogenesis, whereas low-RT cows exhibited higher Methanobrevibacter YE315 abundance, indicative of CO2-utilizing methanogenesis. Additionally, high-RT cows showed increased alternative hydrogen sinks, supported by upregulated genes encoding fumarate reductase, sulfate reductase, nitrate reductase, and ammonia-forming nitrite reductase, thereby reducing hydrogen availability for methanogenesis. Metabolically, high-RT cows had higher propionate concentrations and were enriched with rapid-fermenting bacteria (Prevotella, Sharpea, Veillonellaceae, and Succinivibrionaceae), whereas low-RT cows exhibited higher acetate concentrations with elevated acetate-producing pathways, reflecting differences in energy partitioning mechanisms. This study establishes RT as a microbiome-linked, non-invasive screening tool for identifying low-EME cows. The observed microbial and metabolic shifts in high-RT cows suggest that RT-based selection could enhance methane mitigation, rumen efficiency, and climate-smart livestock production. Leveraging RT-associated microbial profiles offers a scalable and cost-effective approach to reducing EME in cattle.IMPORTANCEMethane emissions from livestock contribute to climate change and reduce animal efficiency. This study reveals that cows with longer rumination times (chewing cud for an extra 94 minutes daily) produce 26% less methane than cows with shorter rumination times. The gut microbiome plays a key role—low-methane cows host microbial communities that produce less methane while efficiently utilizing hydrogen for energy conservation in the rumen. By analyzing rumination sensor data and/or in combination with microbial profiles from rumen or fecal samples, farmers can non-invasively identify and select cows that naturally emit less methane. This scalable, cost-effective strategy offers a practical solution for reducing livestock’s environmental footprint while enhancing efficiency and advancing climate-smart agriculture.